2008
DOI: 10.1037/0022-006x.76.5.820
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to engagement in sleep restriction and stimulus control in chronic insomnia.

Abstract: Sleep restriction (SRT) and stimulus control (SC) have been found to be effective interventions for chronic insomnia (Morgenthaler et al., 2006), and yet adherence to SRT and SC varies widely. The objective of this study was to investigate correlates to adherence to SC/SRT among 40 outpatients with primary or comorbid insomnia using a correlational design. Participants completed a self-report measure of sleepiness prior to completion of a 6-week cognitive behavioral treatment group for insomnia. At the posttre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
60
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(64 citation statements)
references
References 46 publications
1
60
3
Order By: Relevance
“…It was suggested by Morin et al that acceptability will influence "seeking, initiating and adhering to treatment" (p. 302). Extending from this concept, one study found a correlation between patients who perceived Sleep Restriction Therapy or Stimulus Control Therapy as annoying, boring or uncomfortable and lower global adherence scores on a modified version of the Medical Outcomes Study General Adherence Scale (Vincent, Lewycky, & Finnegan, 2008).…”
Section: Engaging With Insomnia Treatments Patient Perceptions Of Trementioning
confidence: 98%
“…It was suggested by Morin et al that acceptability will influence "seeking, initiating and adhering to treatment" (p. 302). Extending from this concept, one study found a correlation between patients who perceived Sleep Restriction Therapy or Stimulus Control Therapy as annoying, boring or uncomfortable and lower global adherence scores on a modified version of the Medical Outcomes Study General Adherence Scale (Vincent, Lewycky, & Finnegan, 2008).…”
Section: Engaging With Insomnia Treatments Patient Perceptions Of Trementioning
confidence: 98%
“…Second, depressive or dysthymic symptoms have been identified as obstacles to adherence, when operationalized as therapist-rated adherence (Vincent & Hameed, 2003), or self-reported adherence to behavioral recommendations (Manber et al, 2011; McChargue et al, 2012) and cognitive components such as changing expectations about sleep (Manber et al, 2011). Third, some evidence suggests that less severe insomnia prior to treatment initiation, as measured by better sleep quality and more sleepiness (potentially an indication of less hyperarousal) is predictive of lower session attendance rates (Morgan, Thompson, Dixon, Tomeny, & Mathers, 2003) and sleep diary-obtained inconsistency in rise time (Vincent, Lewycky, & Finnegan, 2008), respectively. Lastly, some studies have shown those with decreased readiness or motivation for change are more likely to report poorer adherence to sleep hygiene instructions (Hebert, Vincent, Lewycky, & Walsh, 2010) and report poorer adherence to rise time and time in bed recommendations in their sleep diary (Matthews, Schmiege, Cook, Berger, & Aloia, 2012).…”
mentioning
confidence: 99%
“…In aggregate, these studies have shown that self-help interventions, although not as effective as therapistdirected CBTI, are significantly more effective than minimal treatment controls and produce improvements on a variety of sleep indexes. These studies, however, also have highlighted poor treatment adherence to the potent stimulus control and sleep restriction components of CBTI (Vincent, Lewycky, & Finnegan, 2008).…”
mentioning
confidence: 97%